1998
DOI: 10.1103/physrevlett.80.257
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Dichroism in the Electron-Impact Ionization of Laser-Oriented Atomic Sodium

Abstract: We report the first experimental observation of "orientational dichroism" in electron impact-induced ionization. ͑e, 2e͒ experiments have been performed on pure angular momentum states 3P 3͞2 , m F 13 and m F 23 of the sodium atom, excited by right-and left-handed circularly polarized laser light. Our results show that the angular correlation of the final-state electron pair is strongly dependent on the m L sublevel populated. Comparison with calculation demonstrates the dependence of the dichroism on details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Laser excitation by polarized light is another means of selecting a population of molecules with a particular orientation. This technique is applicable to atomic targets, 37,175 but cannot be readily applied to molecules because of a large number of rotational states that are populated at room temperature and the narrow band nature of laser light that limits a fraction of molecules in a sample that can be excited. Inhomogeneous strong electric fields are routinely used to orient the angular momentum vectors of rotating molecules.…”
Section: Molecular Frame Emsmentioning
confidence: 99%
“…Laser excitation by polarized light is another means of selecting a population of molecules with a particular orientation. This technique is applicable to atomic targets, 37,175 but cannot be readily applied to molecules because of a large number of rotational states that are populated at room temperature and the narrow band nature of laser light that limits a fraction of molecules in a sample that can be excited. Inhomogeneous strong electric fields are routinely used to orient the angular momentum vectors of rotating molecules.…”
Section: Molecular Frame Emsmentioning
confidence: 99%
“…In scattering of charged particles from oriented atomic targets (produced, e.g., via optical pumping), the CD effect leads to the dependence of cross sections on the helicity of the laser pump beam [23]. This effect has been observed recently for scattering into the capture channel [24] as well as in cross sections of e-2e impact ionization of atoms assisted by a circularly polarized laser field resonant with an atomic transition [25,26]. New aspects of the CD effect appear in the presence of a static electric field (in addition to a laser field), which induces an anisotropy in an initially isotropic atomic medium.…”
Section: Brief Survey Of Dichroic Effects In Unpolarized Atom Photoprmentioning
confidence: 99%
“…The general features of the frequency dependence of the φ k coefficients discussed above provide an instructive illustration of the so-called threshold phenomena that are predicted by the general theory of multichannel reactions involving a short-range binding potential (see, e.g., [186]). For this kind of potential, in a classic paper [70] Wigner showed that the branchpoint singularity of the reaction amplitude at the threshold energy (E = 0) of a given breakup channel having an orbital angular momentum L causes a universal threshold behaviour of the corresponding breakup cross section: 25) above the opening of this channel. Extending Wigner's analysis, Baz' [187] showed that generally in a multichannel problem the branch-point non-analyticity of the multichannel amplitude at the mth-channel threshold, E m = 0, causes a particular, non-analytic behaviour, or TA, in the partial cross sections of all other open channels, in general.…”
Section: B21 Analytical Properties Of φ ±K (ω) and Threshold Phenomentioning
confidence: 99%
“…they must satisfy the mirror symmetry with respect to the scattering plane mentioned above. The breaking of this symmetry by the target polarization is known as orientational dichroism and it has been observed in electron-impact ionization of polarized sodium [32].…”
mentioning
confidence: 99%